Archiving Historical Data : Three Criticisms for the Reliability of Digital Sources - Raistiwar Pratama (Program Studi Ilmu Perpustakaan UIN Alauddin, 2020)
For data, medium is the information itself, as stated by Marshal McLuhan in 1960’s. What Harold K. Innis would have to assume as “the bias of media”. In the midst of “total history” reawakening and the use of “big data” and “one data,” issues on source criticism towards data are deliberately ignored as soon as online access is open for public. Similar to Heather Sutherland’s “historicizing history” and Samuel Wineberg’s “historical thinking”, principles on records processes are among others efforts to protect historical data. This writing describes source criticisms on digital archival records.